Obstetric admissions to the intensive care unit: a five year review - Pattnaik, Tapan; Samal, Sunita; Behuria, Sasmita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Care of the critically ill obstetric patients is a unique challenge particularly because of its unpredictability. The outcome in these patients would not only contribute to the assessment of the quality of patient care but would also enhance the risk stratification of pregnant patients in the evaluation of new therapies. This study is intended to review a series of critically ill obstetric patients admitted to our ICU to assess the spectrum of disease, required interventions, and maternal outcome, and to identify conditions associated with maternal death. Methods: This retrospective cohort study was conducted in 16-bed medical and surgical ICU in a 500 bedded tertiary care hospital over a period of 5 years (2009-2013) at Bhubaneswar, Odisha, India. Results: Only 54 obstetric patients were admitted to the ICU which constitutes 2.09% of all ICU admissions, 0.78% of emergency obstetric admissions and 0.9% of the total deliveries. Majority of patients (79.62%) were admitted during postpartum period. The leading obstetric indication for ICU admission was obstetric hemorrhages (29.6%). Ectopic pregnancy was common (7 patients) among the obstetric hemorrhages. In the present study maternal mortality was 16.6%, while 70.3% were improved after treatment. The main cause of maternal death was obstetric haemorrhage (55.5%). ICU interventions during the stay of the patients in terms of mechanical ventilation were used in 72.2% of cases. Other interventions included blood & blood product transfusion in 30 (55.5%), inotropes in 34 (62.9%), anti-hypertensive in 14 (25.9%), anticonvulsant in 16 (29.6%) & dialysis in 4 (7.4%) cases. Conclusions: The need of ICU management for obstetric conditions is on rising trend. The need for ventilatory or inotropic support may predict poor outcome. An adequate adoption of safe motherhood initiative would reduce obstetric ICU admissions and thereby will also reduce the maternal mortality.